An Eye for the Tropics : Tourism, Photography, and Framing the Caribbean Picturesque - Thompson, Krista A., 1972- (Book collections on Project MUSE., 2006)
"Images of Jamaica and the Bahamas as tropical paradises full of palm trees, white sandy beaches, and inviting warm water seem timeless. Surprisingly, the origins of those images can be traced back to the roots of the islands' tourism industry in the 1880s. As Krista A. Thompson explains, in the late nineteenth century, tourism promoters, backed by British colonial administrators, began to market Jamaica and the Bahamas as picturesque 'tropical' paradises. They hired photographers and artists to create carefully crafted representations, which then circulated internationally via postcards and illustrated guides and lectures. Illustrated with more than one hundred images, including many in color, An Eye for the Tropics is a nuanced evaluation of the aesthetics of the 'tropicalizing images' and their effects on Jamaica and the Bahamas. Thompson describes how representations created to project an image to the outside world altered everyday life on the islands. Hoteliers imported tropical plants to make the islands look more like the images. Many prominent tourist-oriented spaces, including hotels and famous beaches, became off-limits to the islands' black populations, who were encouraged to act like the disciplined, loyal colonial subjects depicted in the pictures. Analyzing the work of specific photographers and artists who created tropical representations of Jamaica and the Bahamas between the 1880s and the 1930s, Thompson shows how their images differ from the English picturesque landscape tradition. Turning to the present, she examines how tropicalizing images are deconstructed in works by contemporary artists--including Christopher Cozier, David Bailey, and Irenee Shaw--at the same time that they remain a staple of postcolonial governments' vigorous efforts to attract tourists"--Publisher's website.